Gestão de contexto aplicada ao encaminhamento adaptativo em soluções convergentes - SPINOLA, Sergio Sampaio (2015)
Since the advent of Internet, many technological advances have contributed to enable a great variety of services available to network users, among which multimedia video applications and interactive voice were deployed on a huge scale, in a way never been envisioned in Internet before. Several control mechanisms were proposed and developed in order to support these new applications, most of which carried out through extensions of the classical QoS mechanisms, such as extended MPLS networks controls and traffic engineering techniques, which are mostly deployed statically. The massification of mobile devices and laptops with enhanced multimedia capabilities represent a new challenge, in a way that network controls using traditional methods are no longer capable of meeting users' expectations (translated into quality of experience). In opposite, the number of variables that must be dealt with are continously growing, determining the need to define and control what is understood as events and context variables. In addition, effective controls that take into account various parameters such as user's perception should be implemented by adaptive routing in converging solutions. In this work the main goals are: the proposal of a framework for context management applied to adaptive routing, specifically in the design of a context treatment and management processing module. comprising modeling and context representation; modeling of the architecture that embraces the implementation of the proposed solution and the subsequent validation of the implemented architecture for the traffic management of converging applications oriented scenarios. In general, this work focus on the thematic of context oriented network traffic management and control, covering the design life cycle of network scenarios, from modeling through their effective experimentation.